DESAIN KOMUNIKASI VISUAL SEBAGAI STRATEGI PERANCANGAN PROMOSI TOKO PANCING INDO RAYA DI SEMARANG - Febryantahanuji Febryantahanuji; Haryo Kusumo; Hendri Rasminto (MANAJEMEN, 2021)
Nowadays many companies, shops and home industries need promotional media to be known by the wider community. Many promotional media are used to promote a company or product being sold, one of which is brochures, stickers, banners and x-banners. For a company or store that offers its products, brochures, stickers, banners and x-banners serve as promotional media so that people are more familiar with the products being sold and know the latest information related to the promotion of the store or company.One such company or store is the Indo Raya Fishing Shop. Indo Raya Fishing Shop, located in the city of Semarang, is engaged in the sale of fishing equipment and other supporting accessories. In this case, Toko Pancing Indo Raya wants to promote the goods sold in its store and the latest information, which previously only sold wholesale, can now buy in retail or individually. From this problem, the author uses the interview method, namely the author conducts direct talks with the Indo Raya Fishing Shop and the author's observations go directly to the field to find the data needed.Making designs based on existing theories and using design principles and then processing them with computer programs such as Adobe Photoshop Cs3 and Corel Draw X4